Ruqyah SebagaiTerapi Pembimbing Konseling Islam - Chanra Simamora; Naimah Agustina (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2026)
Ruqyah syar’iyyah is a healing method derived from Islamic teachings, performed by reciting verses from the Qur’an and supplications taught by the Prophet Muhammad (peace be upon him). In the context of Islamic counseling, ruqyah can serve as a therapeutic approach to assist individuals facing psychological, spiritual, or emotional disturbances. This study aims to examine the effectiveness of ruqyah as a guiding therapy in the Islamic counseling process. Using a descriptive qualitative approach, data were collected through literature studies, observations, and interviews with ruqyah practitioners and Islamic counselors. The findings indicate that ruqyah provides inner peace, strengthens faith, and serves as a spiritual bridge within the counseling framework. A collaborative effort between counselors and ruqyah practitioners is necessary to ensure safe and Sharia-compliant therapy. These findings support the integration of clinical and spiritual approaches in Islamic counseling practices.